Anti-nuclear antibodies positive serum from systemic lupus erythematosus patients promotes cardiovascular manifestations and the presence of human antibody in the brain - Marie Kelly-Worden; Leslie Hammer; Robyn Gebhard; Lauran Schrader; Marley Griffin; Dalahnna Cooper (Wolters Kluwer Medknow Publications, 2014)
Background: Systemic lupus erythematosus (SLE) is characterized by the presence of anti-nuclear antibodies (ANAs) in the serum of patients. These antibodies may cross over into the brain resulting in the development of neuropsychiatric symptoms and result in abnormal pathology in other organs such as the heart and kidneys. Objective: The objective of this study was to determine if SLE pathology could be detected in the hearts and brains of rats injected with positive human ANA serum. Materials and Methods: Lewis rats (n = 31) were selected for this study due to documented research already performed with this strain in the investigation of serum sickness, encephalitis and autoimmune related carditis. Rats were injected once a week with either ANA positive or negative control serum or saline. Hearts were examined for initial signs of heart disease including the presence of lipid deposits, vegetation, increased ventricular thickness and a change in heart weight. Brains were examined for the presence of human antibody and necrotic lesions. Animals were observed for outward signs of neuropathy as well. Blood samples were taken in order to determine final circulating concentrations of IgG and monitor histamine levels. Results: Animals injected with ANA were significantly higher for lipid deposits in the heart and an increased ventricular thickness was noted. One animal even displayed Libman-Sacks endocarditis. Brains were positive for the presence of human IgG and diffuse internal lesions occurred in 80% of the ANA positive serum injected animals examined. Blood histamine levels were not significantly different, but actually lower than controls by the end of the experiment. Conclusion: Since human antibodies were detected in the brain, further studies will have to identify which antibody cross reactions are occurring within the brain, examine cell infiltration as well as characterize the antibodies associated with more destructive consequences such as lesion formation.